2019
DOI: 10.3390/molecules24234290
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of the Secondary Structure and Biopharmaceutical Formulation of an Active Branched Antimicrobial Peptide

Abstract: The synthetic antimicrobial peptide SET-M33 is being developed as a possible new antibacterial candidate for the treatment of multi-drug resistant bacteria. SET-M33 is a branched peptide featuring higher resistance and bioavailability than its linear analogues. SET-M33 shows antimicrobial activity against different species of multi-resistant Gram-negative bacteria, including clinically isolated strains of Pseudomonas aeruginosa, Klebsiella pneumoniae, Acinetobacter baumanii and Escherichia coli. The secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…At the same time, AMPs or host defense peptides have a potent broad-spectrum antimicrobial action against pathogenic bacteria, fungi, and viruses [ 27 ]. Thus, AMPs and their various combinations are considered as promising candidates for drugs against multidrug-resistant bacteria such as P. aeruginosa , S. aureus , K. pneumoniae or A. baumannii [ 28 , 29 , 30 ].…”
Section: Brief History Of Research Physicochemical Properties CLmentioning
confidence: 99%
“…At the same time, AMPs or host defense peptides have a potent broad-spectrum antimicrobial action against pathogenic bacteria, fungi, and viruses [ 27 ]. Thus, AMPs and their various combinations are considered as promising candidates for drugs against multidrug-resistant bacteria such as P. aeruginosa , S. aureus , K. pneumoniae or A. baumannii [ 28 , 29 , 30 ].…”
Section: Brief History Of Research Physicochemical Properties CLmentioning
confidence: 99%
“…In contrast, Sikora et al described divergent MIC values of AMPs depending on their counter-ions and recommended the testing of peptides with different counter-ions individually [30]. Castiglia et al did not observe any influence of acetate and chloride on MICs, but reported a better solubility of peptide chlorides [32]. In accordance with the present results, the sodium salts of TFA, acetate, and chloride did not show any antimicrobial effects in concentrations up to 1000 µM (Supplementary Materials, Table S1) confirming that the counter-ion has no influence on the antimicrobial activity of Leg1.…”
Section: Influence Of the Counter-ion On The Antimicrobial Activity Of Leg1mentioning
confidence: 98%
“…Error bars reflect ML uncertainties as well as, where applicable, statistical errors due to sampling. Experimental values [64][65][66][67][68][69] are indicated as black stars.…”
mentioning
confidence: 99%
“…Fig. 2 shows a visual representation of the shifts for the polymorphs of succinic acid and glycine for which experimental data is available [64][65][66][67][68][69] (a full table is provided in the Supplemental Information). Even after internal calibration, NQEs lead to changes of the chemical shifts by up to 0.2 ppm for 1 H and 2 ppm for 13 C, in every case reducing the discrepancy with measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation